Area 4 has layer IV in adult primates. (16th April 2014) - García‐Cabezas, Miguel Ángel; Barbas, Helen
Abstract There are opposing views about the status of layer IV in the primary motor cortex (area 4). Cajal described a layer IV in area 4 of adult humans. In contrast, Brodmann found layer IV in developmental but not in adult primates and called area 4 'agranular'. We addressed this issue in rhesus monkeys using the neural marker SMI‐32, which labels neurons in lower layer III and upper layer V, but not in layer IV. SMI‐32 delineated a central unlabeled cortical stripe in area 4 that corresponds to layer IV, which was populated with small interneurons also found in layer IV in 'granular' areas (such as area 46). We distinguished layer IV interneurons from projection neurons in the layers above and below using cellular criteria. The commonly used term 'agranular' for area 4 is also used for the phylogenetically ancient limbic cortices, confusing areas that differ markedly in laminar structure. This issue pertains to the systematic variation in the architecture across cortices, traced from limbic cortices through areas with increasingly more elaborate laminar structure. The principle of systematic variation can be used to predict laminar patterns of connections across cortical systems. This principle places area 4 and agranular anterior cingulate cortices at opposite poles of the graded laminar differentiation of motor cortices. The status of layer IV in area 4 thus pertains to core organisational features of the cortex, its connections and evolution.